The Relationship Between School Well-Being And Adjustment Of Students Of Class 10 in School: Hubungan Antara School Well-Being Dengan Penyesuaian Diri Siswa Kelas 10 di Sekolah - Dessy Ari Susanti; Dwi Nastiti (Academia Open, 2022)
Self-adjustment is one of the factors for achieving harmony between individual self-demands and the environment. School well-being is influential in developing the ability to adapt to each individual. This study aims to determine the relationship and relationship between school well-being and self-adjustment. The population in this study were 413 student of SMA Negeri 1 Mojosari class 10 and the total sample was based on Isaac and Michael’s table with an error rate of 5%, namely 186 students with simple random sampling technique. Collecting research data using 2 psychological scales, namely, the scale of school well-being and the scale of self-adjustment. Research data analysis using product moment correlation. The results of the analysis show that school well-being has positive relationship with self-adjustment in SMA Negeri 1 Mojosari student with a correlation coefficient of 0,956 with a significance level of 0,000 (less than 0,05). The school well-being variabel towards adjustment gave an effective contribution 91,3%.